Online Learning Problems in the Covid-19 Pandemic for English Education Students - Sholihatul Hamidah Daulay; Nurika Khalila Daulay; Abdul Halim Daulay; Reflina Reflina; Siti Maysarah; Dita Khairunnisa (AL-ISHLAH: Jurnal Pendidikan, 2021)
During the Covid-19 pandemic, the teaching and learning process through an online system is one option that can deal with barriers to the teaching and learning process directly to avoid the spread of the virus. This study intends to analyze students’responses to the problems they face during the Covid-19 pandemic and how students deal with online learning during the pandemic. The background of this research is the experience of students with the problems they face during distance learning or online due to Covid-19 which requires students to follow government rules, namely doing distance learning or online. The informants or respondents in this study were several students majoring in . The data collected by the researcher was based on online interviews conducted with 15 students The data analysis used interactive analysis technique by Miles Hubberman. The researcher arranges several questions that must be asked of the participants to obtain the required information. In the online teaching and learning process during the covid-19 pandemic, various problems experienced by students are as follows, the most dominant problem when carrying out online learning is the limited internet network, especially for students who live in rural areas.